STRATEGIES FOR ENHANCING COMMITMENT TO THE ORGANIZATION THROUGH PROGRAMS TO STRENGTHEN TRANSFORMATIONAL LEADERSHIP, SELF-EFFICACY, TEAMWORK, AND JOB SATISFACTION - Susilawati Susilawati; Sri Setyaningsih; Widodo Sunaryo (JF Publisher, 2025)
Teacher absenteeism remains a persistent issue in Indonesia, particularly in madrasah settings, driven by factors such as low income, secondary employment, and dissatisfaction with the work environment. This study explores the influence of transformational leadership, self-efficacy, teamwork, and job satisfaction on organizational commitment among madrasah teachers, both directly and indirectly through job satisfaction. Using a quantitative survey method supported by SITOREM analysis, the research examines structural relationships and identifies key indicators for improvement. The study found moderate explanatory power with R² values of 0.415 for organizational commitment and 0.580 for job satisfaction. Results show that transformational leadership (β = 0.342), teamwork (β = 0.537), and job satisfaction (β = 0.279) have significant direct effects on organizational commitment, while self-efficacy (β = 0.121) has a positive but insignificant effect. Only self-efficacy demonstrated a significant indirect effect (β = 0.154) on commitment through job satisfaction, highlighting job satisfaction as an effective mediator in this pathway. These findings offer practical insight into how school leadership and supportive work environments can strengthen teacher commitment, potentially reducing absenteeism and improving educational outcomes in Indonesian madrasahs.